Analisis Pengembangan Bisnis Bebek Kaleng Awet Madura Dengan Metode Bussiness Model Canvas (BMC) Dan Brand Strategy Canvas (BSC) - Munawaroh, Solehatun; Horisah, Khariratun; Anistasia, Atika (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Ready-to-eat food is one of technological innovation that is increasingly developing in the domestic market due to aspects of efficiency and practicality that benefit consumers. The application of this technology is also targeting the typical Indonesian culinary industry which has great potential to continue to be developed, one of which is the Awet Madura canned duck (Bebek Kaleng Awet Madura) produced by PT Nur Yasin. Given the increasing competition in the food industry, a comprehensive strategy is needed to maintain the existence of quality products and compete in the market. The purpose of this study is to determine the extent of business development of Awet Madura Canned Duck through the Business Model Canvas (BMC) and Brand Strategy Canvas (BSC) approaches and the synergy of the two. The results showed that the synergy between business elements and branding strategies in the product of Awet Madura canned duck is very influential on business progress, so as to create differentiation, attract new customers, and maintain loyalty. With this approach, Awet Madura Canned Duck can combine the advantages of traditional specialty products with modern packaging innovations, making it relevant in the competitive fast food market, both locally and globally. Keywords : Ready-to-eat, Bebek Madura, Bussiness Model Canvas, Brand Strategy Canvas